Radical Reactions in the Gas Phase: Recent Development and Application in Biomolecules. (28th December 2014) - Gao, Yang; Bu, Jiexun; Peng, Zhou; Yang, Biwei
Abstract : This review summarizes recent literature describing the use of gas phase radical reactions for structural characterization of complex biomolecules other than peptides. Specifically, chemical derivatization, in-source chemical reaction, and gas phase ion/ion reactions have been demonstrated as effective ways to generate radical precursor ions that yield structural informative fragments complementary to those from conventional collision-induced dissociation (CID). Radical driven dissociation has been applied to a variety of biomolecules including peptides, nucleic acids, carbohydrates, and phospholipids. The majority of the molecules discussed in this review see limited fragmentation from conventional CID, and the gas phase radical reactions open up completely new dissociation channels for these molecules and therefore yield high fidelity confirmation of the structures of the target molecules. Due to the extensively studied peptide fragmentation, this review focuses only on nonpeptide biomolecules such as nucleic acids, carbohydrates, and phospholipids.